The Impact of Co-curricular Activities on Adolescent Development: A Qualitative Study - Anita Sharma; Tammana Sharma (International Journal of Educational Excellence and Innovation, 2024)
This study explores the impact of co-curricular activities on adolescent development. Through in-depth interviews and focus groups with adolescents, parents, and educators, the research investigates the multifaceted benefits and challenges associated with participation in co-curricular activities. The findings reveal significant positive effects on social skills, academic performance, and emotional well-being, while also highlighting challenges such as time management and stress.